A Review on the Rural Household Energy in China From 1990s—Transition, Regional Heterogeneity, Emissions, Energy-Saving, and Policy - Zhang, Xinxin; Xu, Kaili; He, Maogang; Wang, Jingfu (Frontiers in Energy Research, 2022)
Rural energy is related to the domestic energy supply, consumption, and improvement of living standards of more than one-third of the population in China. In the “14th Five-Year Plan,” it has been clearly pointed out that it is necessary to strengthen the clean utilization of coal and implement the construction of rural clean energy projects. At present, the energy consumption structure of rural areas in China is transiting from traditional solid energy to commercial energy and clean energy. Based on this background, this paper reviews the transition trend, influencing factors, and regional differences of China’s rural household energy consumption structure from the 1990s. Taking into account China’s goal of carbon peaking by 2030 and carbon neutrality by 2060, carbon dioxide and pollutant emissions generated in the process of energy consumption and the energy-saving potential of rural households are analyzed and discussed. Moreover, the evolution of rural energy policies in China is presented and related proposals are also made. This review aims to provide reference for relevant researchers and policy makers.